Bridging Policy and Practice: Evaluating the Curriculum Effectiveness in Fostering Religious Moderation and 21st-Century Competencies - A. Sri Mardiyanti Syam; Ishak Ishak (Jurnal Pendidikan Islam, 2025)
Global educational reforms emphasize holistic development, including character, creativity, and 21st-century skills. In Indonesia, the Merdeka Curriculum drives this shift, particularly through the Project to Strengthen the Profile of Pancasila Students and Rahmatan Lil Alamin (P5-PPRA) initiative designed for madrasah. P5-PPRA aims to foster interdisciplinary learning and embed the values of religious moderation. This study aimed to evaluate the implementation and effectiveness of the P5-PPRA program within madrasahs across South Sulawesi. The study employed the CIPP (Context, Input, Process, Product) evaluation model using a mixed-methods approach. Data were collected from 37 respondents, including teachers, students, and administrators. Quantitative data analysis revealed varied levels of success across the CIPP dimensions: the Context aspect achieved an excellent rating (80.67%). However, the Input (72.3%), Process (68.3%), and Product (74.6%) dimensions were all rated as good. These results indicate conceptual clarity but challenges in operational execution. The P5-PPRA program shows strong contextual fit but requires significant enhancement in its implementation mechanics. The study concludes that achieving excellent outcomes necessitates targeted improvements. It is recommended to strengthen teacher competencies, upgrade essential facilities and infrastructure, and refine evaluation and planning mechanisms. The implications underscore the critical need for continuous, systemic support to boost the sustainability and overall effectiveness of P5-PPRA in fostering holistic education and promoting religious moderation among students.